Application of Ludo Board Game in Increasing the Activeness of the Physics Study Group of Mts DDI Seppange Students - Napsawati Napsawati; Yusdarina Yusdarina (Jurnal Pendidikan Fisika, 2021)
This study aims to describe the activeness of the members of the physics science study group by implementing the Ludo Board Game and seeing the students' responses to the application of the Ludo Board Game in increasing the activity of the members of the physics science learning group. To achieve this goal, descriptive research has been carried out using the Ludo Board Game game. The subjects of this study were students of class VIII MTS DDI Seppange in the 2019/2020 school year, which may be 24 people. The data research method used was observation (observation), questionnaires, interview techniques and documentation. Furthermore, the analysis technique is carried out by means of proportional descriptive data analysis. The results showed that the increase in the activity of students' study groups after the implementation of the Ludo Board Game (LBG). Meanwhile, the students' responses to the application of Ludo Board Game in increasing the activeness of members of the physics science study group were very feasible, namely for the quality of the content with an eligibility level of 81.25% and a 94.53% usage level.